Nanoalumina promotes the horizontal transfer of multiresistance genes mediated by plasmids across genera - Qiu, Zhigang (National Academy of Sciences, 2012)
Antibiotic resistance is a worldwide public health concern. Conjugative transfer between closely related strains or species of bacteria is an important method for the horizontal transfer of multidrug-resistance genes. The extent to which nanomaterials are able to cause an increase in antibiotic resistance by the regulation of the conjugative transfer of antibiotic-resistance genes in bacteria, especially across genera, is still unknown. Here we show that nanomaterials in water can significantly promote the horizontal conjugative transfer of multidrug-resistance genes mediated by the RP4, RK2, and pCF10 plasmids. Nanoalumina can promote the conjugative transfer of the RP4 plasmid from Escherichia coli to Salmonella spp. by up to 200-fold compared with untreated cells. We also explored the mechanisms behind this phenomenon and demonstrate that nanoalumina is able to induce oxidative stress, damage bacterial cell membranes, enhance the expression of mating pair formation genes and DNA transfer and replication genes, and depress the expression of global regulatory genes that regulate the conjugative transfer of RP4. These findings are important in assessing the risk of nanomaterials to the environment, particularly from water and wastewater treatment systems, and in the estimation of the effect of manufacture and use of nanomaterials on the environment.